2013
DOI: 10.3928/19404921-20121219-01
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior, Physical Activity, and Psychological Health of Korean Older Adults with Hypertension: Effect of an Empowerment Intervention

Abstract: The aim of this study was to determine the effect of an 8-week empowerment intervention on sedentary behavior, physical activity, and psychological health in Korean older adults with hypertension. Using a quasi-experimental design, older adults participated in either an experimental group (n = 27) or control group (n = 21). The experimental group received an empowerment intervention including lifestyle modification education, group discussion, and exercise training for 8 weeks, and the control group received s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 39 publications
6
48
0
1
Order By: Relevance
“…In the week following program delivery, participants in the intervention group reduced total and weekday sedentary behavior by approximately 837 min/week and 132 min/ weekday, respectively. This preliminary effect was larger than prior sedentary behavior interventions with older adults using self-reported measures of behavior [5][6][7].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the week following program delivery, participants in the intervention group reduced total and weekday sedentary behavior by approximately 837 min/week and 132 min/ weekday, respectively. This preliminary effect was larger than prior sedentary behavior interventions with older adults using self-reported measures of behavior [5][6][7].…”
Section: Discussionmentioning
confidence: 69%
“…Intervention content focused on disrupting sedentary behavior habits (i.e., an automatic process) via action planning in addition to enhancing self-efficacy, intentions, and plans to limit sedentary behavior via educational content, practicing interrupting sedentary behavior, and developing action plans (i.e., reflective processes). Previous interventions have relied on determinants of physical activity, primarily reflective motivational determinants, to develop intervention content [5,6,8]. The intervention effects in this study may be the result of increased emphasis on targeting and disrupting the automatic motivational processes (e.g., habits) that maintain older adults' sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empowerment theory is one effective theoretical approach for sedentary behavior interventions (Chang, Fritschi, & Kim, 2013). According to this theory, increased self-efficacy, social support, and empowerment influence the behavior of a subject with regard to becoming healthier (Falk-Rafael, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…According to this theory, increased self-efficacy, social support, and empowerment influence the behavior of a subject with regard to becoming healthier (Falk-Rafael, 2001). Previous studies have shown that intervention programs that applied empowerment theory decrease the sedentary behavior of elderly persons with HTN (Chang et al, 2013). In addition, depressive symptoms have been found to be associated with sedentary behavior (Teychenne, Ball, & Salmon, 2010).…”
Section: Introductionmentioning
confidence: 99%